Mastery issues and teaching approaches for the electrical technology certificate programme at community colleges on the topic of measuring instruments - Tee, Tze Kiong; Ramlan, Aryati; Azman, Mohamed Nor Azhari; Bagus, Nur Rahma Putra Andika; Sukardi, Sukardi; Risfendra, Risfendra; Abd Hamid, Ruhiana Idayu (Association of Researcher of Skills and Vocational Training, Malaysia, 2022)
The teaching approach has a significant impact on a student's ability to master a course. The purpose of this study is to identify the level of competence and explore the teaching approaches used by community college lecturers for the Electrical Technology Certificate Programme for the topic of Measuring Instruments. This study employs a qualitative approach with an explanatory research design that includes interview data gathering procedures with eight lecturers who have taught electrical courses before. According to the findings, students' comprehension of the issue of measurement instruments is still at a modest level. While students must learn the concept of measuring instruments, it is a fundamental knowledge. Teaching and learning approach must be adjusted and improved to improve students’ understanding. According to the data, the lecturers' teaching methods are also traditional. Lecturers are enthusiastic about implementing improvements to the teaching and learning process, such as the use of engaging learning modules to increase students' understanding and skills, particularly in the area of measurement instruments.